Pengaruh Personal Hygiene Terhadap Terjadinya Penyakit Kusta di Wilayah Kerja Puskesmas Sukatani Kabupaten Purwakarta Tahun 2020 - Zaelani Ahmad; Anna Sunita; Sri Utami (Universitas Respati Indonesia, 2021)
Indonesia is ranked third in leprosy cases number. Leprosy causes damage to skin, nerves, limbs and eyes. Personal hygiene affects healing success, and about 70% heal itself (determinate). This study aims to determine effect of personal hygiene on leprosy incidence in Sukatani Public Health Center, Purwakarta Regency, 2020. This study used quantitative method with case control design. Data collection techniques using questionnaire. Sample were 116 respondents with ratio 1:3, consist of 29 cases and 87 controls. Sampling technique was based on leprosy cases list at Health Center. Control is closest neighbor. Multivariate analysis using binary logistic regression test. Results showed that there was significant relationship between work type (p=0.023), knowledge (p=0.007), contact history (p=0.000), house’s physical condition (p=0.001), clean water sources (p=0.005), humidity (p=0.006), and room temperature (p=0.028). There is effect of personal hygiene (p = 0.003), with an OR of 4.295 (95% CI: 1.708 - 10.803), meaning that respondents who have poor personal hygiene risked 4.295 times for leprosy compared to respondents who have good personal hygiene, after being controlled by contact history, knowledge, room humidity, house’s physical condition, and working type. It is recommended to improve population personal hygiene through health promotion regarding knowledge of leprosy, as well as the provision of clean water sources.